Correlation between the 4Cs and motivation to become volunteers among nursing students - Yakobus Siswadi; Bima Adi Saputra; Kinanthi Lebdawicaksaputri (PAGEPress Publications, 2024)
During the COVID-19 pandemic, there was a surge in public enthusiasm for volunteering, including among nursing students from the Faculty of Nursing at Universitas Pelita Harapan (UPH). The UPH nursing faculty has a foundational framework known as competence, compassion, commitment, and character (4Cs), which serves as the basis for shaping each student's personality. This study aimed to explore how the 4Cs foundational framework motivates students to become COVID-19 volunteers. Using a quantitative descriptive design with a cross-sectional approach to data collection, the study focused on UPH nursing students who volunteered for COVID-19 relief efforts, with a sample size of 100 respondents. Data analysis was conducted using Somers Δ. The findings revealed that the majority of respondents exhibited adequate motivation to volunteer, with 60% falling into this category, while 22% showed a high level of motivation. Notably, the factors of commitment (p=0.004) and character (p=0.009) demonstrated a strong correlation with encouraging nursing students to volunteer. Conversely, competence and compassion did not show a significant correlation with students' motivation to volunteer. Among the four driving factors, only commitment and character were statistically related to students' motivation to become volunteers.